PENGARUH PIDATO TERHADAP PERILAKU SOSIAL ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Aisya Amini; Zulkifli N; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the results of observation on the social behavior of students have not developed optimally. So it is necessary to apply the speech technique. The purpose of this study is to know the effect of speech towards social behavior of children aged 5-6 years at TK Negeri Pembina 1 Pekanbaru. The method of this research used experimental method with using one group pre-test post-test design. The samples used in this study were 14 students. The data collection technique used is observation. Technique of data analysis used t-test by using program of SPSS 16.0. The research hypothesis was to find the influence of speech towards social behavior of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru. Based on data analysis was known that tcalculated = 11,248 > ttable = 2,160 with Sig. (2-tailed) = 0.000. Because Sig < 0,05 it can be concluded that there is difference of social behavior that was be done before and after the of speech. It can be interpreted that there is influence of speech towards social behavior of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru significant that is equal to 58,38%. Keyword: Social Behavior, Speech